Community Participation by People with Chronic Obstructive Pulmonary Disease. (3rd September 2021) - Malaguti, Carla; Holland, Anne E.; McDonald, Christine F.; Mahal, Ajay; Alison, Jennifer A.; Hill, Catherine J.; Zanaboni, Paolo; O'Halloran, Paul; Bondarenko, Janet; Macdonald, Heather; Barker, Kathryn; Crute, Hayley; et al.
Abstract: Little is known regarding community participation in individuals with chronic obstructive pulmonary disease (COPD). The aim of this study was to explore community participation in individuals with COPD and to determine whether there is an association between community participation and activity-related outcome variables commonly collected during pulmonary rehabilitation assessment. We also sought to investigate which of these variables might influence community participation in people with COPD. Ninety-nine individuals with COPD were enrolled (67 ± 9 years, FEV1 : 55 ± 22% predicted). We assessed community participation (Community Participation Indicator (CPI) and European Social Survey (ESS) for formal and informal community participation), daily physical activity levels (activity monitor), exercise capacity (6-minute walk test), breathlessness (Modified Medical Research Council, MMRC scale), self-efficacy (Pulmonary Rehabilitation Adapted Index of Self-Efficacy) and anxiety and depression (Hospital Anxiety and Depression Scale). Higher levels of community participation on the CPI were associated with older age and greater levels of physical activity (total, light and moderate-to-vigorous) (all rs = 0.30, p < 0.05). Older age and more moderate-to-vigorous physical activity independently predicted greater community participation measured by CPI. Higher levels of depression symptoms were associated with less formal and informal community participation on ESS ( rs = –0.25). More formal community participation on ESS was weakly ( rs = 0.2–0.3) associated with older age, better lung function, exercise capacity and self-efficacy, and less breathlessness. Self-efficacy, exercise capacity, and age independently predicted formal community participation in individuals with COPD. Strategies to optimize self-efficacy and improve exercise capacity may be useful to enhance community participation in people with COPD.